AJRAKH - THE ANCIENT BLOCK PRINTING TEXTILE CRAFT OF INDIA - Pandey, Anjali (International Journal of Research -GRANTHAALAYAH, 2025)
The cotton fabrics of India ornamented by dyeing, painting and block printing were a major part of international trade for many centuries, spreading through the maritime routes of the Indian Ocean to the Arab world and Southeast and East Asia in medieval times. Ajrak is the oldest form of block Printing . It is recognized as a tradition of Sindhi culture. These prints are mostly found in Sindh in Pakistan and Ajrakhpur and Barmer in India. All ingredients in Ajrakh are derived from nature, be it botanical essences or common minerals. It is one of the madar other block printing methods. It has undergone some changes in the production of traditionally two-sided durable block printed cotton fabrics.Indigo blue and red are the predominant colors used in the Ajrakh print. 1 Editor Muthu SS & Gardetti Miguel Angel Sustainability in textiles and apparel industry PG 7.